Effect of Altitude on Adult Emergence, Pupal Mortality and Adult Sex Ratio of Chinese Citrus Fly, Bactrocera minax (Enderlein) (Diptera:Tephritidae) - Karki, Bipin; Thapa, Resham Bahadur; Adhikari, Debraj; Gautam, Bhola; Shedai, Amrita (Journal of Agriculture and Environment, 2023)
Problems of Chinese Citrus Fly (CCF), Bactrocera minax (Enderlein) in citrus orchards have been increasing in Nepal. The reason behind the failure in CCF control is the lack of a clear and thorough understanding of the adult emergence period in different altitudes. Therefore, the pupae of CCF were collected from the soil below the infested sweet orange trees in Sunapati Rural Municipality, Ramechhap, Nepal and reared in containers of height 5 cm and diameter 6 cm (10 pupae per container) in randomized complete block design selecting different locations as treatments, viz. 1247 masl (Bethan), 1354 masl (Nagsiwa), 1443 masl (Aarukharka), 1561 masl (Sadi), 1650 masl (Dimipokhari) replicating four times. Early peak emergences of adult CCF (four weeks earlier in 4th week of April) occurred at lower altitudes as compared to the higher altitudes (in 4th week of May), where peak-emergence was recorded. Male: female ratio (range 1.05-1.37) did not differ significantly at different altitudes, while pupal mortality (25%) was found to be the highest in upper elevations. The study concludes that fly management strategy should be made according to the date of emergence at least two weeks earlier at lower elevations than in higher elevations.